Regulation of bone formation by baicalein via the mTORC1 pathway - Li SF; Tang JJ; Chen J; Zhang P; Wang T; Chen TY; Yan B; Huang B; Wang L; Huang MJ; Zhang ZM; Jin DD (Dove Medical Press, 2015)
Sheng-fa Li,1,2,* Jia-jun Tang,1,2,* Jian Chen,1–3,* Pei Zhang,4,* Ting Wang,5 Tian-yu Chen,1,2 Bo Yan,1,2 Bin Huang,1,2 Liang Wang,1,2 Min-jun Huang,1,2 Zhong-min Zhang,1,2 Da-di Jin1,21Academy of Orthopedics of Guangdong Province, Guangzhou, People’s Republic of China; 2Department of Orthopedics, The Third Affiliated Hospital, Southern Medical University, Guangzhou, Guangdong, People’s Republic of China; 3Three Gorges Central Hospital of Chongqing, Chongqing, People’s Republic of China; 4School of Traditional Chinese Medicine, Southern Medical University, Guangzhou, Guangdong, People’s Republic of China; 5Department of Cell Biology, School of Basic Medical Science, Southern Medical University, Guangzhou, Guangdong, People’s Republic of China*These authors contributed equally to this workAbstract: Osteoporosis is a systemic skeletal disease that is characterized by low bone density and microarchitectural deterioration of bone tissue. The increasing prevalence of osteoporosis has attracted much attention. In this study, MC3T3-E1 pre-osteoblasts were treated with the natural compound, baicalein (0.1 µmol/L, 1 µmol/L, 10 µmol/L), to stimulate differentiation over a 14-day period. In addition, a canonical ovariectomized (OVX) mouse model was used to investigate the effect of 3-month baicalein treatment (10 mg/kg per day) in preventing postmenopausal osteoporosis. In vitro, we found that baicalein induced activation of alkaline phosphatase, stimulated the mammalian target of rapamycin complex 1 (mTORC1) signaling pathway, and induced expression of osteoblast differentiation markers, ie, osteocalcin, osterix, collagen Iα1, and runt-related transcription factor 2 (RUNX2), in osteoblasts. In vivo, several bone parameters, including trabecular thickness, trabecular bone mineral density, and trabecular number, in the distal femoral metaphysis were significantly increased in OVX mice treated intragastrically with baicalein for 3 months compared with OVX mice that were not treated with baicalein. We also found that expression of osteocalcin and RUNX2 was decreased in primary ossified tissue from the OVX group, and baicalein increased the levels of osteocalcin and RUNX2 in OVX mice. These data suggest that baicalein can stimulate MC3T3-E1 cells to differentiate into osteoblasts via activation of the mTORC1 signaling pathway, which includes protein kinases and transcription factors such as P-4E/BP1 and P-S6K1.Keywords: osteoblast, osteoporosis, menopause, mTOR